EVALUATING THE IMPACT OF THE FREE CIVIL SERVICE EXAMINATION REVIEW PROGRAM: A CITY COLLEGE OF CALAMBA AND CITY GOVERNMENT COLLABORATION (Proceedings of the International Conference on Future of Education, 2025)
A local college demonstrated its commitment to social responsibility by offering a free civil service review program, aiming to build the capacity of local government employees and the community, aligning with the college's mission to drive positive change. This study assessed the sustainability of this community extension program, specifically the joint CCC-CGC Civil Service review, where initially 303 participants registered, with 184 completing the survey, and their profiles were analyzed based on sex, civil status, age, and employment location. The evaluation covered four key areas: overall assessment, reviewers, lecture materials, and the review program itself, with statistical analysis using ANOVA conducted to determine differences in evaluations across these areas, revealing a normal distribution (Shapiro-Wilk p = 0.973) and homogeneity of variances (p = 0.725). Overall, participants rated all four areas as "very satisfactory," however, two significant findings emerged: evaluations of the reviewers’ area differed significantly (p = 0.028) between CGC employees and participants from outside Calamba, and the evaluation of the program's benefits and convenience varied significantly (p = 0.019) across age groups, particularly with participants aged 38-42 and 52-57 rating this aspect as only "satisfactory." The study recommends continuing the program while addressing identified weaknesses, specifically improvements in lecture materials and extended program duration, and suggests future research should explore the program's impact on actual Civil Service exam scores.
Keywords: civil service review; community extension; reviewer; lecture materials; review program; exam preparation; capacity building